The semantics of the Norwegian modal auxiliary verbs - Mikučionis, Ugnius (Kalbotyra, 2007)
In this paper, I have tried to show that the meanings of Modern Norwegian modal verbs may best be described in terms of gradable scales (clines) both with respect to epistemic and non-epistemic modality. Epistemic modality deals with the degree of commitment; Deontic modality – “ – degree of moral desirability; Dynamic modality – “ – degree of readiness. The use of such gradable scales (clines) enables us to draw a semantic map which adequately covers the relevant semantic area – and to make some hypotheses about the diachronic development of the meanings of the Norwegian modal verbs.